Contribution to the Methodology of the Determination of the Thermal Conductivity Coefficients Λ of Materials Applied in the Railway Subbase Structure - Libor Izvolt; Peter Dobes; Martin Mecar (Communications - Scientific letters of the University of Zilina, 2013)
The paper focuses on the methodology of determination of thermal conductivity coefficients λ of the construction materials of railway subbase. The determination of the thermal conductivity coefficients λ depends on the determination of the specific heat capacity and the time interval as sub-parameters. The paper presents specialized equipment for the determination of these parameters, the stated procedures and the method of test evaluation.The paper focuses on the presentation of the results of the experimental determination of the thermal conductivity coefficients λ of selected construction materials (clay, track ballast, fraction 32/63 mm, crushed aggregate fraction 0/32 mm and sandy gravel 0/32 mm). In the conclusion there is the confrontation of the values of the thermal conductivity coefficients λ stated by the experimental laboratory measurements with the values stated in TNZ 73 6312 and STN EN ISO 10 456.